2020
DOI: 10.1177/1091581820961498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reverse Transcriptase Inhibitors on Proliferation, Apoptosis, and Migration in Breast Carcinoma Cells

Abstract: High telomerase activity in human breast cancer is associated with aggressive tumors resulting in decreased survival. Recent studies have shown that telomerase inhibitors may display anticancer properties in some human cancer cell lines. In the present study, we examined the effects of 4 reverse transcriptase inhibitors (RTIs), used for the treatment of HIV; Abacavir (AC), Lamivudine (LV), Stavudine (SV), and Tenofovir (TF) on proliferation, apoptosis, and migration in the normal human mammary epithelial cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
9
0
3
Order By: Relevance
“…Carlini and coworkers ( Carlini et al, 2010 ) investigated the effect of abacavir in prostate cancer cell lines and observed that abacavir reduced cell growth, migration, and invasion processes. Another study investigated the effect of abacavir and its combination with other reverse transcriptase inhibitors in breast cancer cells and found an increase in apoptosis and a decrease in migration in treated cells ( Sekeroglu et al, 2021 ). On the other hand, Exemestane is already used in breast cancer, but Koutras and colleagues ( Koutras et al, 2009 ) observed the antiplatelet effect of Exemestane also in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Carlini and coworkers ( Carlini et al, 2010 ) investigated the effect of abacavir in prostate cancer cell lines and observed that abacavir reduced cell growth, migration, and invasion processes. Another study investigated the effect of abacavir and its combination with other reverse transcriptase inhibitors in breast cancer cells and found an increase in apoptosis and a decrease in migration in treated cells ( Sekeroglu et al, 2021 ). On the other hand, Exemestane is already used in breast cancer, but Koutras and colleagues ( Koutras et al, 2009 ) observed the antiplatelet effect of Exemestane also in lung cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MTT assay was performed as previously published 3,12 . Results were expressed as percent inhibition relative to control cells.…”
Section: Methodsmentioning
confidence: 99%
“…This resistance is an important problem for aggressive and poor prognosis cancers. Cancer cells can activate various mechanisms to evade the cytotoxicity of the drugs by altering or enhancing drug efflux, apoptotic pathways, or DNA repair mechanisms 2,3 . Eventually, the resistance of tumor cells to chemotherapy drugs leads to failure of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Lamivudine has been shown to enhance the sensitivity of liver cancer cell lines to chemotherapy with sorafenib, by decreasing partially the expression of an apoptosis inhibitor (cIAP2), thus diminishing the viability of liver cancerous cells ( 46 ). Moreover, in cultured cancerous cell lines from human breast cancer it was also found that Lamivudine, combined with other ANNAs such as Abacavir, Stavudine, and Tenofovir, significantly increased apoptosis and decreased migration more effectively in the cancerous cell lines than in normal breast cell lines ( 47 ). This opens the possibility for further research to find the optimal combinations of ANNAs to decrease viability and migration of particular types of cancerous cells and tumors.…”
Section: Repurposing Nucleoside/nucleotide Antivirals In Cancermentioning
confidence: 99%